Pendidikan Agama dan Kekerasan pada Anak (Child Abuse) Perspektif Pendidikan Islam - Muhamad Tisna Nugraha (PSGA LP2M IAIN Pontianak, 2015)
The case of violences in education is often seen in Indonesia. The education institution should appropriately be the place to create the real mankind. Furthermore, it also prepares the smart generation, emotionally and spiritually. Despite it is not always a core of student development. Moreover, the abuse acts always happening are the indicator that the education process is still far from humanity values. Education, furthermore, is not only the obligation of spiritual dedication, especially for Moslem man and woman, but also as a place that should produce the scholars. Besides, they are prepared for accomplishing the humanity problems, for instance, poverty, idiocy, suppression, and terrorism. Therefore, education contributes to prevent and reduce conflict. Then, it is also designed specifically to counter violences. Overall, a concept of effective education of applying the study method absorbed by religious and cultural values.